Mesenchymal Stem Cell-Derived Small Extracellular Vesicle as A Novel Therapeutic Approach for Chemotherapy-Induced Male Infertility: A Review Article - Maryam Taher; Hanieh Jalali; Homa Mohseni Kouchesfehani; Gholamreza Kaka (International Journal of Fertility and Sterility)
Small extracellular vesicles (sEVs) have been recognized as a promising therapeutic modality due to their low immunogenicity, and the ability to penetrate biological barriers. They contain significant amounts of lipids, proteins, and microRNAs, effectively participating in intra- and inter-cellular communications. sEVs derived from mesenchymal stem cells (MSCs) are being explored as a potential therapeutic option due to their immunomodulatory, anti-inflammatory, antioxidant, and regenerative properties, offering advantages over stem cell transplantation-based treatments. Chemotherapy induces side effects on various organs, particularly those with high proliferative capacity, such as testicular tissue. Exposure to some groups of chemotherapeutic agents, such as cyclophosphamide, cisplatin, and doxorubicin can cause DNA damage and induce apoptosis in spermatogonia and primary spermatocytes. Chemotherapy has been shown to induce cellular stress in testicles, leading to testicular dysfunction and the activation of apoptotic pathways in response to external and internal stress. The current research aims to review the potential therapeutic advantages of sEVs derived from MSCs in addressing sperm abnormalities and male infertility resulting from chemotherapy. Several lines of evidence indicate that treatment with sEVs can reduce testicular tissue damage caused by chemotherapy by decreasing oxidative stress and inflammatory responses. sEVs boost the growth and motility of spermatogenic cells and protect them from apoptosis by activating internal pathways. Therefore, as a non-invasive approach, they have shown promising results in regenerating damaged spermatozoa and restoring spermatogenesis.